Association between the obesogenic environment and the occurrence of overweight/obesity in school adolescents (Research, Society and Development, 2020)
To evaluate the association between the obesogenic environment and the occurrence of overweight / obesity among adolescents. Case-control study conducted between July and October 2018, with adolescents (10 to 16 years) enrolled in public schools. “Cases” were defined as those who were overweight or obese, as “controls” the eutrophic, paired by sex, age and class. Demographic characteristics and those related to the obesogenic environment (using a form), in addition to the nutritional status of caregivers and adolescents (through anthropometry) were evaluated. Pearson's chi-square test was applied, with Fisher adjustments, when necessary. SPSS 22.0 and a 95% confidence interval were used. Study approved by the Research Ethics Committee (CAAE 84019518.3.0000.5187). The nutritional status of caregivers was associated with that of adolescents (p